HUBUNGAN POLA ASUH IBU DENGAN KEMANDIRIAN ANAK USIA 3-5 TAHUN DI TK BANTENGAN KAB MADIUN TAHUN 2018 - Ika, Ika Ayu Purnamasari (Jurnal Kesehatan Madani Medika (JKMM), 2019)
Early childhood is a period where practically the dependence has been through and is replaced by independence. Independence is greatly influenced by the parenting pattern of parents, especially mother. The children who are close to their mother will be easier in getting friends and are able to be independent and sociable. The purpose of this study was to determine the association between mother’s parenting pattern and the independence of 3-5 years old children in Bantengan Kindergarten, Madiun Regency. This research used descriptive correlation study with cross sectional approach. The samples of this study were mothers with 3-5 years old children in Bantengan Kindergarten, Madiun Regency district as many as 84 respondents. Sampling technique used total sampling. Data of parenting pattern and child's independence were gathered by questionnaire for mothers with 3-5 years old children. The data analysis used Chi Square Test with α = 0.05. The results of study indicated that an authoritarian parenting of mother mostly had enough independence that was 9 people (40.9%). Democratic parenting of mother mostly had a good independence that was 26 people (60.5%) and permissive parenting of mothers mostly had less independence that was 8 people (42.1%). Based on Chi Square test, there was a correlation between parenting pattern of mother and independence of 3-5 years old children in Bantengan Kindergarten, Madiun Regency (p value = 0.046). It is recommended for parents to choose parenting pattern which can develop and improve the independence of children, through love and affection, build independence of children, and develop good communication between mother and children